1995
DOI: 10.1111/j.1476-5381.1995.tb13228.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of vasoconstrictor 5HT1‐like receptors revealed by precontraction of rabbit isolated mesenteric artery

Abstract: 1 A series of 5-hydroxytryptamine (5-HT) receptor agonists including 5-HT, 5-carboxamidotryptamine (5-CT) and sumatriptan produced little or no contraction of rabbit isolated mesenteric arteries under resting tone conditions, even at concentrations up to 10-4 M. 2 When the same agonists were retested in mesenteric artery preparations pre-contracted with the thromboxane-mimetic, U46619, each demonstrated concentration-related vasoconstrictor activity. 5-CT and 5-HT were especially potent and effective in this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Furthermore, sumatriptan has been shown to cause contraction, via a 5-HTlD-like receptor, in a range of isolated vascular smooth muscle preparations presumably through increases in [Ca2+Ji (Parsons et al, 1992;Choppin & O'Connor, 1995). To our knowledge this is the first paper describing the coupling of an endogenous 5-HTlB receptor to increases in [Ca2+Ji through a PTX-sensitive mechanism.…”
Section: -Ht1 Receptor Mdiated Increases In [Ca2i2895mentioning
confidence: 90%
“…Furthermore, sumatriptan has been shown to cause contraction, via a 5-HTlD-like receptor, in a range of isolated vascular smooth muscle preparations presumably through increases in [Ca2+Ji (Parsons et al, 1992;Choppin & O'Connor, 1995). To our knowledge this is the first paper describing the coupling of an endogenous 5-HTlB receptor to increases in [Ca2+Ji through a PTX-sensitive mechanism.…”
Section: -Ht1 Receptor Mdiated Increases In [Ca2i2895mentioning
confidence: 90%
“…Different mechanisms may underlie PGF 2␣ -induced potentiation of ␣ 1 -ARmediated response. It has been reported that the vasoconstriction induced by stimulation of some receptors can be enhanced, or even uncovered, by increasing tone through Gq protein-coupled receptor pathway (Choppin and O'Connor, 1995;Movahedi and Purdy, 1997). Several studies have shown that the vasoconstriction induced by ␣-AR stimulation can be potentiated by agonists of other G protein-coupled receptors (Fabi et al, 1998;Bhattacharya and Roberts, 2003).…”
mentioning
confidence: 99%
“…However, much of the information on the vascular effects of sumatriptan has been derived from studies using peripheral vascular serotonin receptors. For example, sumatriptan-induced peripheral vascular contraction has been widely studied in the rabbit saphenous vein (9), femoral artery (4), mesenteric artery (5), and iliac artery (36). Because the cardiovascular liabilities of sumatriptan may be related to its ability to constrict coronary arteries (23), sumatriptan has also been studied in coronary arteries from dogs (21) and humans (1).…”
mentioning
confidence: 99%